Ability, Motivation, Opportunity Enhancement Practices: Which SHRM Practice Is More Influential to Employee Turnover? - Kalyani, M.W; Chong, S.C (The Mattingley Publishing Co, 2020)
Talented and skilled employees are vital to the success of any organisation. Lack of human resources strategies for developing skills, motivating teams and above all, lack of understanding of needs of employees have contributed to the increased rate of employee turnover. This research aims to empirically examine the three strategic human resource management (SIIRM) enhancement practices, i.e. ability, motivation and opportunity from the resource-based perspective to determine which practice is more influential to employee turnover in the banking sector. Data were collected from senior managers, human resource managers and executives in Sri Lanka by employing a self-administered questionnaire which were subsequently analysed using structural equation modelling. The findings from 238 respondents suggest that all the three SHRM practices exerted significant effect on employee turnover, in the order of ability enhancement practices, motivation enhancement practices and opportunity enhancement practices. The results imply that SHRM practitioners should bear in mind the coherence between the three practices, giving emphasis to improving work abilities of employees and building a positive work environment, as well as providing more opportunities for talents to utilise their work experiences. The findings also fetched several theoretical implications which are elaborated in the paper.
Keywords: Ability enhancement practices, Banking sector, motivation enhancement practices, opportunity enhancement practices.